Osteonecrosis of the jaw in patients taking atorvastatin: case series - Nordin, Jenizan; Ghazali, Ahmad Badruddin (IIUM Press, 2022)
Osteonecrosis of the jawbones commonly seen in patients taking bisphosphonates, denosumab, and several antiangiogenic medications with several oral factors such as tooth extraction or dental infection. Currently, patients taking Simvastatin, a medication commonly used to treat hypercholesteremia, were reported of developing osteonecrosis of the jaw. Thus, it is important that clinicians know about the risk of osteonecrosis for patients taking this hypercholesteremia medication. It is not known if the undesirable effect only occurs with Simvastatin or other types of statin medication. We report in detail three cases of osteonecrosis of patients taking Atorvastatin calcium, a second-generation statin medication.